2022
DOI: 10.21203/rs.3.rs-1983080/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In silico identification of potential inhibitors of vital monkeypox virus proteins from FDA approved drugs

Abstract: The World Health Organization (WHO) recently declared the monkeypox outbreak ‘A public health emergency of international concern’. The monkeypox virus belongs to the same Orthopoxvirus genus as smallpox. Although smallpox drugs are recommended for use against monkeypox, monkeypox-specific drugs are not yet available. Drug repurposing is a viable and efficient approach in the face of such an outbreak. Therefore, we present a computational drug repurposing study to identify the existing approved drugs which can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…An in silico study revealed that the compound fludarabine is a potential inhibitor of the MPV target DNA-dependent RNA polymerase subunit (A6R) along with two other targets, protein catalysing the envelopment of intracellular mature virus particles (F13L) and proteins involved in cell entry (D8L) (Altayb, 2022). Sahoo et al, identified four potential inhibitors, Tipranavir, Cefiderocol, Doxorubicin, and Dolutegravir towards the targets thymidylate kinase and D9 (decapping enzyme) (Sahoo et al, 2022) (Table 1).…”
Section: Virus-host Interactionmentioning
confidence: 99%
“…An in silico study revealed that the compound fludarabine is a potential inhibitor of the MPV target DNA-dependent RNA polymerase subunit (A6R) along with two other targets, protein catalysing the envelopment of intracellular mature virus particles (F13L) and proteins involved in cell entry (D8L) (Altayb, 2022). Sahoo et al, identified four potential inhibitors, Tipranavir, Cefiderocol, Doxorubicin, and Dolutegravir towards the targets thymidylate kinase and D9 (decapping enzyme) (Sahoo et al, 2022) (Table 1).…”
Section: Virus-host Interactionmentioning
confidence: 99%